The Role of Subjective Well-Being in Mediating Grit and Academic Stress Among Final-Year Students at University X - Ardis, Nurfaidah; Nugraha, Summed P; Nasution, Salsabila; Raisardhi, Abid; Nasir, Ehsan (Indonesian Journal of Counseling and Development, 2025)
Academic difficulties faced by final-semester students often lead to academic stress, which can hinder thesis progress. This study aimed to investigate the role of Subjective Well-Being (SWB) in mediating the relationship between Grit and academic stress among final-semester students at University X in Makassar. A total of 319 students participated in the study, including 214 women and 105 men. Data were collected using the Educational Stress Scale for Adolescents (ESSA) to measure academic stress, the Grit-S Scale to assess Grit, and the Positive and Negative Affect Schedule (PANAS) and Satisfaction with Life Scale (SWLS) to measure SWB. Data were analyzed using the Medmod technique in Jamovi software. The results showed that SWB could be a mediator between Grit and academic stress (path coefficient = 0.559, p < 0.01), and SWB explained 50% of the total effect, indicating partial mediation. Furthermore, the correlation analysis revealed a strong positive correlation between Grit and SWB (r = 0.665, p < 0.01), and between SWB and academic stress (r = 0.600, p < 0.01). Practical implications of this study include the need for universities to implement programs that enhance students' Grit and SWB, such as mental resilience training and self-regulation support. These interventions could help students manage academic stress more effectively, improving both their academic performance and overall well-being. The study emphasizes the need for mental health support for final-semester students as they complete their thesis